Impact of Growth Plans and Quality Costs on Performance Companies - Hadita Hadita (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
The objective of this study is to examine the impact of growth plans and quality costs on the performance of companies. The study sample consisted of 30 individuals, specifically managing authorities and ship construction professionals, who were affiliated with several shipyard enterprises in Jakarta. The sampling methodology employed is the census sampling method, which involves the utilization of all members of the population as samples. The major data utilized in this study was collected through the distribution of questionnaires to all participants. The employed methodology for data analysis encompasses descriptive statistical analysis, validity testing, reliability testing, and classical assumption testing. The latter includes normality testing, heteroscedasticity testing, multicollinearity testing, and autocorrelation testing. Additionally, all hypotheses are examined through partial testing, simultaneous testing, and coefficient of determination testing. The findings of this study suggest that the implementation of a growth plan has a statistically significant and favorable impact on enhancing the performance of PT Indonesian Ship Industry (Persero) in Jakarta. Similarly, there exists a positive and statistically significant correlation between the variable of quality cost and the performance of PT. Indonesian Ship Industry (Persero) in Jakarta. This implies that by investing in quality, there is a potential for significant enhancement in firm performance.